The evolutionary nature of accounting and the accounting profession - Grażyna Voss; Paweł Modrzyński (Zeszyty Teoretyczne Rachunkowości)
Purpose: The aim of the article is to analyze the evolution of the accounting profession in the context of contemporary technological, social, and regulatory challenges, as well as to identify key determinants of these changes based on a literature review and survey analysis.Methodology/approach: The study employs a mixed-method approach, combining a literature review in the field of accounting with an analysis of survey results collected from members of the Polish Association of Accountants. This approach integrates theoretical insights with practical findings.Findings: The research highlights that the accounting profession is evolving under the influence of digitization, globalization, and changing regulatory frameworks. Key drivers include technologies such as blockchain, ERP systems, and ESG reporting, which redefine traditional accounting roles and emphasize strategic tasks. The surveys also revealed that professional ethics and interdisciplinary competencies are crucial for modern accountants.Research limitations/implications: The study’s limitations include the non-representative nature of the sample and its focus on the Polish accounting environment. The findings suggest a need for further comparative research at the international level, particularly in the context of regulatory harmonization and technological advancements.Originality/value: This article makes a unique contribution to the field of accounting by integrating an analysis of technological, social, and regulatory determinants with an ethical and interdisciplinary perspective. It emphasizes the importance of adapting to new technologies and evolving societal expectations.